Expression of lncRNA MSC-AS1 in hepatocellular carcinoma cell lines and its effect on proliferation, apoptosis, and migration - Xiaoni Kou; Xiaoni Kou; Jiang Zhu; Xinke Xie; Mingxia Hao; Yingren Zhao (Turkish Journal of Gastroenterology, 2020)
Background/Aims: This study aimed to explore the expression of long non-coding RNA MSC-AS1 in hepatocellular carcinoma (HCC) cells and its effect on the proliferation, migration, and apoptosis of HCC cells. Materials and Methods: The expression of MSC-AS1 in HCC cell lines BEL7402, SMMC7721, Huh7, HepG2, MHCC97-H, and normal hepatocyte line L02 was detected by reverse transcriptase polymerase chain reaction. The HCC cells were divided into blank, negative control (NC)–small interfering RNA (siRNA) (transfected with negative siRNA), and MSC-AS1 siRNA (transfected with MSC-AS1 siRNA) groups. Cell counting kit-8 and colony formation assays were used to determine the proliferation, and cell apoptosis, migration, and invasion were detected by flow cytometry, wound healing, and transwell assays, respectively. Western blot was used to detect the expression of related proteins. Results: The expression of MSC-AS1 in HCC cell lines was significantly higher than that in L02. In the MSC-AS1 siRNA group, the proliferation and colony formation of HCC cells were inhibited, whereas the apoptosis rate was significantly higher than that in the blank and NC-siRNA groups. The rate of wound healing and the number of invasion cells in the MSC-AS1 siRNA group were significantly lower than that in the blank and NC-siRNA groups. Conclusion: MSC-AS1 was upregulated in HCC cells, and the downregulation of MSC-AS1 could inhibit cell proliferation, migration, and invasion and promote apoptosis of HCC cells.Cite this article as: Kou X, Zhu J, Xie X, Hao M, Zhao Y. Expression of lncRNA MSC-AS1 in hepatocellular carcinoma cell lines and its effect on proliferation, apoptosis, and migration. Turk J Gastroenterol 2020; 31(12): 860-7.